READING IN ENGLISH AS A FOREIGN LANGUAGE: RELATIVE CONTRIBUTIONS OF VOCABULARY AND PHONOLOGICAL AWARENESS - Ihata, Anne; Ihata, Takaaki (PEOPLE: International Journal of Social Sciences, 2017)
This study was designed to examine the relative contributions to EFL learners’ reading comprehension of vocabulary size and phonological awareness, potentially significant for the mainly Japanese university students who were the subjects of the study, because of the transfer of L1 reading behaviors which may interfere with fluent reading in English which is a growing necessity for the ‘global human resources’ Japan needs to participate fully in international society. Since both vocabulary size and pronunciation are known to be related to reading skill, this study measured learners’ vocabulary size, phonemic distinction ability, and reading comprehension ability, all using well-known standard tests. A further test of general awareness of English phonology, suggested by Coulson et al. (2013), was also carried out. The results were then statistically examined for any possible correlations, and what they might tell us about the relationships between these various abilities. Although no evidence was found to support a strong relationship between vocabulary alone and reading comprehension, there were indications of interaction between phonological awareness and vocabulary. A relationship between aural phonological distinction ability and reading comprehension was clearly indicated, and there was strong evidence of an effect for the subjects’ first language. These results suggest that phonological knowledge does, indeed, have a part to play in reading comprehension, and possibly reading speed. This underlines the importance of reading aloud practice and encouraging learners’ to acquire accurate pronunciation when teaching reading.